MEMBANGUN DATABASE MENGGUNAKAN MICROSOFT ACCESS 2007 - Dewi Anggraeni; Safrian Aswati; Sri Rezeki Maulina Azmi; Akmal Akmal; Muthia Dewi; Khairil Anwar (STMIK Royal, 2018)
Abstract: Community Service is done in the year 2017 period 2 at SMP Swasta Taman Siswa Kisaran, with the theme